Teaching Writing to Build Studentsâ€™ Character by Using Google Docs - Maria Cholifah (Universitas Kanjuruhan Malang, 2014)
the government of the Republic of Indonesia is now launching a form of education which is based on character known as â€œcharacter educationâ€.Â In the context of character education in schools, it is expected that all the courses taught in all levels and in all kinds of education are directly to the building of good character. To relate with teaching English, writing is one of the subject that has promising potential to help the students to build their character. On the other hand, technology especially internet has been familiar with the students. Via internet we can exchange our idea online, even with people half a world away from us. Google docs is one of the alternative tool that can be used in teaching writing. Google docs is a free online program that allows users to create documents, spreadsheets and presentations online and share them with others for collaboration. By using Google docs the teacher can improve the students writing skill and also build their character.Â Keywords : character building, writing, google docs